Genome-wide analysis of transcriptome and histone modifications in Brassica napus hybrid - Ma, Meng; Zhong, Wenying; Zhang, Qing; Deng, Li; Wen, Jing; Yi, Bin; Tu, Jinxing; Fu, Tingdong; Zhao, Lun; Shen, Jinxiong (Frontiers in Plant Science, 2023)
Although utilization of heterosis has largely improved the yield of many crops worldwide, the underlying molecular mechanism of heterosis, particularly for allopolyploids, remains unclear. Here, we compared epigenome and transcriptome data of an elite hybrid and its parental lines in three assessed tissues (seedling, flower bud, and silique) to explore their contribution to heterosis in allopolyploid B. napus. Transcriptome analysis illustrated that a small proportion of non-additive genes in the hybrid compared with its parents, as well as parental expression level dominance, might have a significant effect on heterosis. We identified histone modification (H3K4me3 and H3K27me3) variation between the parents and hybrid, most of which resulted from the differences between parents. H3K4me3 variations were positively correlated with gene expression differences among the hybrid and its parents. Furthermore, H3K4me3 and H3K27me3 were rather stable in hybridization and were mainly inherited additively in the B. napus hybrid. Together, our data revealed that transcriptome reprogramming and histone modification remodeling in the hybrid could serve as valuable resources for better understanding heterosis in allopolyploid crops.